RETRACTED: The role of the therapist and neurologist in pain management in patients suffering from cardiovascular diseases - Ivashchenko T.V.; Vartanyan V.A.; Sevriugina E.A.; Chkareuli D.N.; Kazakova M.S. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001